2017
DOI: 10.3389/fvets.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Link between Biofilm Formation and the Ability of Pathogenic Salmonella Strains to Colonize Multiple Host Species

Abstract: Salmonella are important pathogens worldwide and a predominant number of human infections are zoonotic in nature. The ability of strains to form biofilms, which is a multicellular behavior characterized by the aggregation of cells, is predicted to be a conserved strategy for increased persistence and survival. It may also contribute to the increasing number of infections caused by ingestion of contaminated fruits and vegetables. There is a correlation between biofilm formation and the ability of strains to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 185 publications
(299 reference statements)
2
71
1
1
Order By: Relevance
“…Biofilms have demonstrated roles in bacterial persistence and virulence [12,13,58,59] and have been 490 anecdotally reported in Clostridia to be composed of cellulose exopolysaccharides [7,8]. Additionally, the 491 loci encoding the molecular machinery for Pel polysaccharide has been recently identified in members of…”
mentioning
confidence: 99%
“…Biofilms have demonstrated roles in bacterial persistence and virulence [12,13,58,59] and have been 490 anecdotally reported in Clostridia to be composed of cellulose exopolysaccharides [7,8]. Additionally, the 491 loci encoding the molecular machinery for Pel polysaccharide has been recently identified in members of…”
mentioning
confidence: 99%
“…Interestingly, representative species of the two cellulose operon lineages identified in HGT events, e.g. the plant and human pathogens, D. dadantii and S. enterica , respectively, are known to produce structurally distinct forms of cellulose with different properties and roles in pathogenesis(77,78). Furthermore, we identified that BcsB divergence was also seen to accompany the rearrangement or horizontal transfer of these operons, which further suggests that it may play a key role in the fine-tuning of cellulose production by coordinating the export of growing cellulose polymers through the periplasm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the csgD is a transcriptional protein that activates the biosynthesis and expression of both curli and cellulose. CsgD activates transcription of the csgBAC operon, which encodes curli structural subunits, and transcription of adrA gene, involved in cellulose biosynthesis (Brombacher et al, 2006;MacKenzie et al, 2017).…”
Section: Csga Gene For Detection Of Curli Fimbria Gene (Biofilm)mentioning
confidence: 99%